USE OF VIRTUAL LABORATORIES IN STUDY OF BIOCHEMISTRY BY STUDENTS OF NATURAL FACULTIES - Ilkevych, Natalya (Journal of Information Technologies in Education (ITE), 2022)
The biochemistry course is one of the basic scientific disciplines studied by students of the chemical and biological specialties of pedagogical universities. Its importance for the methodological training of teachers is growing due to the increase in the volume of biochemical content in school courses in organic chemistry and general biology. The purpose of the article is to describe and analyze the capabilities of virtual laboratories that can be used in the study of the discipline "Biochemistry" by students of natural faculties. The advantages and disadvantages of using such services, features, prospects and examples of their use are given. Among the large number of virtual labs available to Internet users STAR (Software Tools for Academics and Researchers) – a program of the Massachusetts Institute of Technology, Wolfram Demonstrations Project, The ChemCollective and Virtual Labs are selected. The choice of the most suitable services for use was based on the following requirements: free, no registration, an intuitive interface, the ability to use it on any computer connected to the Internet. The possibilities of computer animation allow the student to form a visual image of the spatial structure of complex natural compounds. Selected virtual laboratories contain material necessary to prepare for laboratory exercises, demonstration videos on YouTube, as well as guidelines for laboratory work and materials that can be used for preparing reports, presentations, in independent and remote work and while mastering complex biochemical processes and phenomena. To check and assess the knowledge of students after mastering the laboratory practice with the involvement of virtual laboratories for testing. According to the results of the assignments, the number of students with a high level of mastering the material increased from 10 to 14%, and the number of students who received marks of more than 74 points for completing the tests – from 54 to 78%. The use of virtual laboratories can significantly improve the quality of education.